Family Resilience in Coastal Java Communities in the Context of Climate Change: Perspectives from Walsh and Islamic Law - Zaenurrosyid, A; Azhar, Alias; Hasanah, Uswatun; Sholihah, Hidayatus (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
This study aims to explore various patterns of family resilience influenced by diverse interpretations of fiqh within Javanese coastal Muslim communities. The significance of this study is underscored by the impact of climate change along the north coast of Java, particularly due to the cross-national toll road project, which causes tidal flooding in Bonang, Demak, affecting family resilience in the coastal areas of Java. This qualitative research employs a socio-anthropological approach alongside Islamic law. Data were collected from religious leaders (kyai), village officials, and Muslim families across four coastal villages in Bonang, Demak, Central Java. The data collection techniques included semi-structured interviews and direct observation, supplemented by relevant documents and references. The research identifies three primary findings: Firstly, various forms of resilience among coastal Muslim families in North Java are uniquely shaped by the impacts of climate change. Secondly, the effects of climate change have fostered a new understanding that emphasizes integration and equality in the rights and responsibilities of husbands and wives. Thirdly, the family resilience models of coastal communities in the islands of Java are based on interpretations of family fiqh influenced by economic capacity, education, and social networks. This study contributes to the development of a dynamic understanding of fiqh that impacts the resilience of coastal community families in adapting to the challenges posed by climate change. Further recommendations include strengthening the economic capacity of coastal families through the provision of progressive education to enhance the religious and social resilience networks of coastal Muslim families.